2014
DOI: 10.1002/ajh.23767
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of warm autoimmune hemolytic anemia in adults: New insights based on a single‐center experience with 60 patients

Abstract: Warm autoimmune hemolytic anemia (wAIHA) is a rare autoimmune disease with poorly known natural history and management remaining mainly empirical. To better describe the characteristics and outcome of wAIHA in adults, we performed a single-center cohort study of patients diagnosed with wAIIHA from 2001 to 2012 in our center. Sixty patients (50% women) were included, the mean age at the time of wAIHA onset was 54 6 23 years. wAIHA was considered "primary" for 21 patients (35%) and was associated with an underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
146
3
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(167 citation statements)
references
References 21 publications
11
146
3
7
Order By: Relevance
“…Roumier et al (19) found that only 3.3% of patients with common AIHA did not require treatment, and that approximately half of healthy adults with warm AIHA that developed following an initial cytomegalovirus infection attained spontaneous remission in the follow-up (20). In AIHA induced by a viral infection, the rate of spontaneous remission with decreased infection is likely to be high.…”
Section: Discussionmentioning
confidence: 99%
“…Roumier et al (19) found that only 3.3% of patients with common AIHA did not require treatment, and that approximately half of healthy adults with warm AIHA that developed following an initial cytomegalovirus infection attained spontaneous remission in the follow-up (20). In AIHA induced by a viral infection, the rate of spontaneous remission with decreased infection is likely to be high.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have been smaller in size or descriptive [5,26,27], done in the context of specific hyper coagulable states [28,29], or with a design that excluded secondary AIHA patients or lacked anon-AIHA cohort matched for relevant AIHA risk factors [14][15][16][17]19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the thermal range at which the auto antibodies are most active, AIHA is classified as warm (wAIHA), cold (cold agglutinin disease, or CAD), or mixed. 50-60% of AIHA cases are believed to be secondary [3][4][5]. Major risk factors for secondary AIHA include malignancy [6], viral and mycoplasma infections [7,8], and rheumatologic disorders [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mean number of packed RBC units was 3.9 at the AIHA onset and 10 during clinical follow-up, no transfusion-related adverse events were observed. 34 Das et al transfused 14 WAIHA patients with severe anemia reflected by hemoglobin values ranging from 3.3 to 6.5 g/dL, and reported that only one individual presented chills with no other adverse effects of transfusion observed. 28 The association of WAIHA with other illnesses has also to be considered before indicating transfusion because patients with cardiac disease show less tolerance to acute anemia thus RBC transfusions must be performed to maintain the hemoglobin at a clinically acceptable level until other measures to stop the hemolysis can take effect.…”
Section: Indications For Transfusion In Aihamentioning
confidence: 99%
“…These symptoms generally occur in patients with very profound anemia showing hemoglobin levels below 5 g/dL (Table 4). 1,6,17,18,28,34 In mild or moderate anemias (Hb>8 g/ dL) RBC transfusion is rarely necessary or desirable, as symptoms generally are controlled with appropriated therapy. For patients showing hemoglobin level between 5 and 8 g/dL the clinical decision for transfusion is more difficult.…”
Section: Indications For Transfusion In Aihamentioning
confidence: 99%